Characteristics of Staphylococcus aureus isolated from patients in Busia County Referral Hospital, Kenya - Obanda, B.A.; Cook, Elizabeth A.J.; Fèvre, Eric M.; Bebora, L.; Ogara, W.; Wang, S.-H.; Gebreyes, W.; Ngetich, R.; Wandede, D.; Muyodi, J.; Blane, B.; Coll, F.; et al. (MDPI, 2022)
Staphylococcus aureus is an important pathogen associated with hospital, community, and livestock-acquired infections, with the ability to develop resistance to antibiotics. Nasal carriage by hospital inpatients is a risk for opportunistic infections. Antibiotic susceptibility patterns, virulence genes and genetic population structure of S. aureus nasal isolates, from inpatients at Busia County Referral Hospital (BCRH) were analyzed. A total of 263 inpatients were randomly sampled, from May to July 2015. The majority of inpatients (85.9%) were treated empirically with antimicrobials, including ceftriaxone (65.8%) and metronidazole (49.8%). Thirty S. aureus isolates were cultured from 29 inpatients with a prevalence of 11% (10.3% methicillin-susceptible S. aureus (MSSA), 0.8% methicillin resistant S. aureus (MRSA)). Phenotypic and genotypic resistance was highest to penicillin-G (96.8%), trimethoprim (73.3%), and tetracycline (13.3%) with 20% of isolates classified as multidrug resistant. Virulence genes, Panton-Valentine leukocidin (pvl), toxic shock syndrome toxin-1 (tsst-1), and sasX gene were detected in 16.7%, 23.3% and 3.3% of isolates. Phylogenetic analysis showed 4 predominant clonal complexes CC152, CC8, CC80, and CC508. This study has identified that inpatients of BCRH were carriers of S. aureus harbouring virulence genes and resistance to a range of antibiotics. This may indicate a public health risk to other patients and the community.